A Review of Redox Electrolytes for Supercapacitors - Zhang, Le; Yang, Shuhua; Chang, Jie; Zhao, Degang; Wang, Jieqiang; Yang, Chao; Cao, Bingqiang (Frontiers in Chemistry, 2020)
Supercapacitors (SCs) have attracted widespread attention due to their short charging/discharging time, long cycle life, and good temperature characteristics. Electrolyte has been considered as a key factor affecting the performance of SCs. It largely determines the energy density based on its decomposition voltage and the power density from its ionic conductivity. In recent years, redox electrolytes obtained a growing interest due to an additional redox activity from electrolyte, which offers increased charge storage capacity in SCs. This article summarizes the latest progress in the research of redox electrolytes, and focuses on their properties, mechanisms and applications based on different solvent types available. It also proposes potential solutions for how to effectively increase the energy density of the SCs while maintaining their high power and long life.